Enhancing Ru dispersion and catalytic stability via nitrogen-doped mesoporous carbon supports for biomass-derived FDCA production - Kandasamy, Prabu; Gogoi, Pranjal; Venugopalan, Aswathy Thareparambil; Pandey, Pragati; Raja, Abhishekram; Manikandan, Marimuthu; Raja, Thirumalaiswamy (Inorganic Chemistry Communications, 2026)
The rational design of efficient and selective nanostructured catalysts represents a key strategy for transforming biomass-derived feedstocks into value-added chemicals and fuels. 5-hydroxymethylfurfural (HMF) has emerged as one of the most promising platform chemicals due to its versatile reactivity and potential to be transformed into a wide range of value-added products. Herein, we report the preparation of Ru nanoparticles supported on both N-free and N-doped mesoporous carbon via wetness impregnation, and their application in the catalytic oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA) under mild reaction conditions. The 3wt% Ru-NMC-2 catalyst afforded complete HMF conversion with 83% yield of FDCA at 110 degrees C within 10 h under 10 bar O2. Our research reveals that the nitrogen content in the carbon matrix imparts basicity to the catalyst support, stabilizing smaller Ru metal nanoparticles and helping to maintain a higher metal dispersion (66%), thereby enhancing FDCA yield and turnover frequency. Furthermore, XPS analysis demonstrated that N doping in the carbon matrix would aid in stabilizing the higher availability of metallic Ru compared with nitrogen-free counterparts. The recyclability of the catalyst was demonstrated over 5 cycles, and it exhibited satisfactory catalytic performance towards FDCA yield.
Keywords: 5-Furandicarboxylic acid (FDCA); 5-hydroxymethylfurfural (HMF); biomass valorization; Metal-support interactions; nitrogen-doped carbon; Ruthenium catalysts